Understanding narrative inquiry: the crafting and analysis of stories as research - Kim, Jeong-Hee (Sage, 2016)
Understanding Narrative Inquiry: The Crafting and Analysis of Stories as Research is a comprehensive, thought-provoking introduction to narrative inquiry in the social and human sciences that guides readers through the entire narrative inquiry process—from locating narrative inquiry in the interdisciplinary context, through the philosophical and theoretical underpinnings, to narrative research design, data collection (excavating stories), data analysis and interpretation, and theorizing narrative meaning. Six extracts from exemplary studies, together with questions for discussion, are provided to show how to put theory into practice. Rich in stories from author Jeong-Hee Kim’s own research endeavors and incorporating chapter-opening vignettes that illustrate a graduate student's research dilemma, the book not only accompanies readers through the complex process of narrative inquiry with ample examples, but also helps raise their consciousness about what it means to be a qualitative researcher and a narrative inquirer in particular.